Religiusitas Yesus di Tengah Yang Lain Dari Perspektif Emmanuel Levinas - Norma Selfi Tanaem; Akwila Priska Ibu; Julio Eleazer Nendissa (Institut Agama Kristen Negeri Toraja, 2022)
Abstract: This paper discusses the religiosity of Jesus among others from Levinas's perspective. Existentialist philosophy understands the